1978
DOI: 10.1017/s0021859600055349
|View full text |Cite
|
Sign up to set email alerts
|

Lodging studies in Lolium perenne grown for seed: 2. floret site utilization

Abstract: SummaryIn these experiments lodging not only decreased the number of seeds harvested, but also had an effect in determining which spikelets on the ear set most seed. These data have also shown that many more seeds are set than are harvested, even when the crop is not lodged. It is suggested that there is a lack of assimilate supply to fill the developing seeds, some of which abort, allowing the remainder to attain a viable seed weight. Mechanical support of the crop may increase the assimilate supply to the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2

Year Published

1988
1988
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 7 publications
1
17
2
Order By: Relevance
“…However, in this study in various environments on average 73 to 83 percent of the observed florets contained a seed . Moreover, seed set percentages in perennial ryegrass reported by Anslow (1963) : 65%, Beddows (1931) : 53.9%, Burbidge et al . (1978) : 60%, Griffiths & Lewis (1967) : 62% and Jenkin (1931) : 92 .9% do not support this theory.…”
Section: Seed Abortionmentioning
confidence: 93%
“…However, in this study in various environments on average 73 to 83 percent of the observed florets contained a seed . Moreover, seed set percentages in perennial ryegrass reported by Anslow (1963) : 65%, Beddows (1931) : 53.9%, Burbidge et al . (1978) : 60%, Griffiths & Lewis (1967) : 62% and Jenkin (1931) : 92 .9% do not support this theory.…”
Section: Seed Abortionmentioning
confidence: 93%
“…Anslow (1963 ; and Burbidge et al . (1978) mentioned a decline in successful fertilization within a spikelet from the basal to the distal floret .…”
Section: Introductionmentioning
confidence: 92%
“…Florets may be pollinated but not fertilized, either due to incompatibility or to poor weather conditions for pollen germination or tube growth . Florets may become fertilized, but embryos or developing seeds may abort (Burbidge et al ., 1978 ;Hill, 1980) . Seeds may shatter before harvest (Anslow, 1964 ;Elgersma et al ., 1988 ;Stoddart, 1964) or be lost during harvesting and cleaning (Meijer, 1985) .…”
Section: Introductionmentioning
confidence: 99%
“…This decline may be associated with assimilate reallocations via the stems to the inflorescence in the period of anthesis. Florets closer to nutritional resources are favored to develop a saleable seed (Burbridge et al 1978).…”
Section: Number Of Seeds Per Spikeletmentioning
confidence: 99%